Peran Olahraga dalam Mendorong Perubahan Sosial di Kalangan Generasi Muda - Isah Dwi Putri Siregar; Anjelianus Gulo; David Oktafianus Mendrofa; Idam syafitri gea; Irvan Rizcki Mendrofa; Borisman Zebua; Adam Juelham Baim; Yosefat Herbrema Ginting; Yan Indra Siregar, S.Pd., M.Pd; Putra Amira, S.Pd., M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sports are one of the social activities that have a major influence on the development of young generations, both physically, mentally, and socially. Amid globalization and technological advancements that bring various changes to society, young people face numerous social challenges such as increasing individualism, juvenile delinquency, low social awareness, drug abuse, and violence. In such conditions, sports serve not only as a means of recreation and health improvement but also as a medium for character building and positive social change. This article aims to analyze the role of sports in encouraging social change among young generations through the development of social values, the enhancement of solidarity, the strengthening of social integration, and the prevention of deviant behavior.This study uses a qualitative method with a literature study approach by examining various scientific sources such as books, journals, academic articles, and previous research related to sports and social change. The data were analyzed descriptively to understand the relationship between sports participation and the social behavior development of young people. The results of the study indicate that sports make a significant contribution to shaping discipline, responsibility, teamwork, sportsmanship, and tolerance. In addition, sports activities are able to create inclusive social interaction spaces that strengthen relationships among individuals from different social, cultural, and economic backgrounds.Sports also play an important role in reducing negative adolescent behavior by providing positive activities that divert young people from deviant acts such as fighting, drug abuse, and criminal behavior. Through sports activities, young generations gain opportunities to develop their potential, increase self-confidence, and build leadership and social solidarity. However, the implementation of sports as a means of social change still faces several challenges, including the lack of adequate sports facilities, limited support from society and government, and unequal access to sports for all groups. Therefore, cooperation among the government, educational institutions, families, and communities is needed to create sustainable and inclusive sports programs. Thus, sports can become a strategic instrument in developing a healthy, well-characterized young generation capable of making positive contributions to social life and society.